The Practice of Financial Data Collection in the “Talitihan/Gantangan” Tradition in Wedding Receptions in Gantar District According to Islamic Law - Fajar Kurnia; Imam Prawoto; Rizal Maulana (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This article presents the findings of a study on the financial data gathering practiced by the gantangan people in rural Gantar District when hosting wedding festivities. This research was conducted utilizing a qualitative research method with a descriptive phenomenological approach that use life experience as a tool to better understand socio-culture by gathering data through observations, interviews, and recording, which is then evaluated to reach conclusions. The financial data collection mechanism has both advantages and disadvantages. An advantage is our willingness to help our fellow humans, while the disadvantages are what cause some individuals to complain about this talitihan/gantangan tradition, i.e. when the individual in question is not present but must still pay. The findings of the study indicate that people of Babakan Plasah Village, Gantar District, collect financial data on the talitihan/gantangan tradition as part of the celebrations' execution. No particular record exists for this record. The use of this custom is consistent with Islamic law, as the underlying principle promotes a spirit of assistance in conformity with Islamic principles.